Pancreatic anastomosis after pancreatoduodenectomy: a position statement by the International Study Group of Pancreatic Surgery (ISGPS) - Shrikhande, Shailesh Vinayak; Hackert, Thilo; Büchler, Markus W. (Surgery, 2017)
Background: Clinically relevant postoperative pancreatic fistula (grades B and C of the ISGPS definition) remains the most troublesome complication after pancreatoduodenectomy. The approach to management of the pancreatic remnant via some form of pancreatico-enteric anastomosis determines the incidence and severity of clinically relevant postoperative pancreatic fistula. Despite numerous trials comparing diverse pancreatico-enteric anastomosis techniques and other adjunctive strategies (pancreatic duct stenting, somatostatin analogues, etc), currently, there is no clear consensus regarding the ideal method of pancreatico-enteric anastomosis. Methods: An international panel of pancreatic surgeons working in well-known, high-volume centers reviewed the best contemporary literature concerning pancreatico-enteric anastomosis and worked to develop a position statement on pancreatic anastomosis after pancreatoduodenectomy. Results: There is inherent risk assumed by creating a pancreatico-enteric anastomosis based on factors related to the gland (eg, parenchymal texture, disease pathology). None of the technical variations of pancreaticojejunal or pancreaticogastric anastomosis, such as duct-mucosa, invagination method, and binding technique, have been found to be consistently superior to another. Randomized trials and meta-analyses comparing pancreaticogastrostomy versus pancreaticojejunostomy yield conflicting results and are inherently prone to bias due to marked heterogeneity in the studies. The benefit of stenting the pancreatico-enteric anastomosis to decrease clinically relevant postoperative pancreatic fistula is not supported by high-level evidence. While controversial, somatostatin analogues appear to decrease perioperative complications but not mortality, although consistent data across the more than 20 studies addressing this topic are lacking. The Fistula Risk Score is useful for predicting postoperative pancreatic fistula as well as for comparing outcomes of pancreatico-enteric anastomosis across studies. Conclusion: Currently, no specific technique can eliminate development of clinically relevant postoperative pancreatic fistula. While consistent practice of any standardized technique may decrease the rate of clinically relevant postoperative pancreatic fistula, experienced surgeons can have lower postoperative pancreatic fistula rates performing a variety of techniques depending on the clinical situation. There is no clear evidence on the benefit of internal or external stenting after pancreatico-enteric anastomosis. The use of somatostatin analogues may be important in decreasing morbidity after pancreatoduodenectomy, but it remains controversial. Future studies should focus on novel approaches to decrease the rate of clinically relevant postoperative pancreatic fistula with appropriate risk adjustment.